Human Trafficking Crimes from the Perspective of the Police, Prosecutors, and the Witness and Victim Protection Agency - Farhan Fathur Rahman; Ilham Beni Hamadi Hrp; Rossy Al Jabar; Muhammad Rafli Batu Bara (ISNU Sumatera Utara, 2025)
Human trafficking constitutes a serious form of exploitation for commercial purposes and is widely regarded as a manifestation of modern slavery. Despite the existence of victims’ apparent consent in certain cases, such consent does not negate the exploitative nature of the crime, as victims are often placed in positions where refusal is impossible. In Indonesia, the persistence and increasing number of human trafficking cases raise significant concerns regarding the effectiveness and quality of law enforcement. As a response to global and national commitments, Indonesia has ratified the Palermo Protocol through Law No. 14 of 2009 and strengthened its domestic legal framework through Law No. 21 of 2007 on the Eradication of the Crime of Human Trafficking. Law enforcement efforts in combating human trafficking involve multiple institutions, including the police, the public prosecutor’s office, and the Witness and Victim Protection Agency (LPSK). The police are responsible for investigation and uncovering trafficking networks, while prosecutors exercise dominus litis authority during prosecution, including asset confiscation, license revocation, and restitution for victims. Meanwhile, LPSK plays a vital role in ensuring the physical, psychological, and procedural protection of victims. This study employs a normative juridical research method with qualitative analysis, examining statutory regulations and legal doctrines related to human trafficking. The research aims to assess the effectiveness of law enforcement practices, identify existing obstacles, and emphasize the urgency of integrated, victim-oriented approaches to achieve substantive justice and improved governance in handling human trafficking crimes.